Preparation and Characterization of High Stability Polyurea MicroPCMs Using a Two-step Method of Adding DETA by Interfacial Polymerization (Journal of Fiber Bioengineering and Informatics, 2013)
Butyl stearate and polyurea resin polymerized via toluene-2, 4-diisocyanate (TDI) and diethylenetriamine (DETA) were respectively used as the core material and the shell material in preparingMicroPCMs. The phase change properties, chemical structure, surface morphology and particle sizeand size distribution of microcapsules were investigated by using DSC, FTIR, SEM and Malvern laserparticle size analyzer. The results show that the prepared MicroPCMs were smooth and compact. Theirmelting temperature and enthalpies were 23.3 °C and 79.7 J ⋅ g^{-1} respectively. The average diameterof microencapsulated PCM (MicroPCMs) is in the range of 4.5 ˜ 10.2 μm under the stirring speed of3000 ˜ 6000 rpm. Furthermore, a two-step method of adding DETA was firstly presented, through thismethod, the heat stability and ethanol wash stability of the MicroPCMs has been greatly improved, andthe shell of MicroPCMs prepared by the two-step method has better stability and compactness thanone-step method.
Keywords: Microcapsule; Phase Change Material; Polyurea; Butyl Stearate; Interfacial Polymerization